(untitled) (Journal of Engineering, 2021)
In this paper, the characteristics of microstrip monopole antennas are studied firstly in free space. Secondly, the effects of the human body on the studied antenna’s performance are investigated for wearable communications. Different patch shapes of microstrip monopole antenna are chosen to operate at two bands: industrial scientific and medical band (ISM) and ultra-wideband (UWB) for wearable applications. The studied antenna consists of a radiating element on one side of the substrate and a partial ground plane on the other side. The antenna is supposed to fabricate on cloth fabric whose relative dielectric constant is Ɛr =1.7. At the same time, the pure copper could be used as the conducting part representing both the radiating monopole and the partial ground plane. The software program of Computer Simulation Technology (CST) for Microwave Studio (MWS) is utilized to simulate the studied antennas. The obtained results have illustrated that in the free space, the proposed antennas of slotted hexagonal, rectangular, and circular shapes can operate from 2-12 GHz and of the bandwidth of 10.31 GHz, 10.19 GHz, and 9.67 GHz, respectively. The hexagonal antenna is selected and proposed to investigate the effects of the human body on its performance. The human body is simulated, and its effects on the performance of the proposed antenna are studied. The reflection coefficient, Voltage Standing Wave Ratio (VSWR), gain, and efficiency are found over that frequency range. The simulated results indicate that the human body effects are significant, and the proposed antenna showed to be a good candidate for wearable communications.